Integration of clinical outcomes and molecular features in extramedullary disease in multiple myeloma - Rie Nakamoto-Matsubara; Valentina Nardi; Nora Horick; Tsuyoshi Fukushima; Ryan S. Han; Rajib Shome; Kiyosumi Ochi; Cristina Panaroni; Keertik Fulzele; Farah Rexha; Andrew R. Branagan; Diana Cirstea; et al. (Blood Cancer Journal, 2024)
Abstract Multiple myeloma (MM) remains incurable despite novel therapeutics. A major contributor to the development of relapsed/refractory and resistant MM is extraosseous extramedullary disease (EMD), whose molecular biology is still not fully understood. We analyzed 528 MM patients who presented to our institution between 2014 and 2021 and who had undergone molecular testing. We defined EMD as organ plasmacytoma distinct from bones and evaluated patients for the development of EMD with the goal of defining their molecular characteristics. Here, we show that RAS/BRAF mutations are likely essential for the development of EMD. Our results also indicate that the underlying reason for the negative outcomes in patients with poor prognostic factors such as duplication 1q and deletion 17p is largely due to the development of EMD. However, the presence of TP53 mutation remains a poor prognostic factor regardless of EMD development. Furthermore, mutation sites of TP53 were different between EMD versus non-EMD patients, with gain-of-function mutations enriched in patients with EMD. Our data highlights distinct molecular abnormalities in patients with EMD and provides potential mechanistic insights for novel therapeutic targets for the future.